American slave, American hero : York of the Lewis and Clark Expedition - Pringle, Laurence P. (Calkins Creek Books, 2006)
Presents an account of how William Clark's slave, York, helped during the Lewis and Clark Expedition, discussing the man's skills, strength, and intelligence.